2017
DOI: 10.7717/peerj.2957
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, ecological, and physiological responses of ringed seals to an abrupt decline in sea ice availability

Abstract: To assess whether demographic declines of Arctic species at the southern limit of their range will be gradual or punctuated, we compared large-scale environmental patterns including sea ice dynamics to ringed seal (Pusa hispida) reproduction, body condition, recruitment, and stress in Hudson Bay from 2003 to 2013. Aerial surveys suggested a gradual decline in seal density from 1995 to 2013, with the lowest density occurring in 2013. Body condition decreased and stress (cortisol) increased over time in relation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 72 publications
1
47
1
Order By: Relevance
“…Changes in body condition have also been reported in several other marine predators in the Beaufort Sea ecosystem, which have been hypothesized to reflect an increase in secondary productivity and a decrease in the availability of Arctic cod (Boreogadus saida), an important forage fish and the main prey of the beluga population (Harwood et al, 2015;Loseto et al, 2009). Reductions in body condition of ringed seals, Pusa hispida (Ferguson et al, 2017), and polar bears, Ursus maritimus (Stirling and Derocher, 2012), and mortality events in walrus, Odobenus rosmarus (Fischbach et al, 2009), have similarly been associated with climate-induced loss of sea ice. Reductions in sea ice not only affect habitat use by Arctic whales but have also facilitated the northward migration of temperate species (Bouchard et al, 2017;Falardeau et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Changes in body condition have also been reported in several other marine predators in the Beaufort Sea ecosystem, which have been hypothesized to reflect an increase in secondary productivity and a decrease in the availability of Arctic cod (Boreogadus saida), an important forage fish and the main prey of the beluga population (Harwood et al, 2015;Loseto et al, 2009). Reductions in body condition of ringed seals, Pusa hispida (Ferguson et al, 2017), and polar bears, Ursus maritimus (Stirling and Derocher, 2012), and mortality events in walrus, Odobenus rosmarus (Fischbach et al, 2009), have similarly been associated with climate-induced loss of sea ice. Reductions in sea ice not only affect habitat use by Arctic whales but have also facilitated the northward migration of temperate species (Bouchard et al, 2017;Falardeau et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…In contrast, southern seals invested more into offspring at an earlier age to take advantage of more productive environmental conditions (Stearns, 1992). In the south, seals cycled seasonally from high blubber storage (up to 60% of body mass) to very low body condition (30% blubber) that likely threatened their survival (Ferguson et al, 2017;Ferguson et al, 2018;Young & Ferguson, 2013). Progeny born into southern regions likely encountered good feeding conditions during the open-water season allowing for faster growth and earlier reproduction, with shorter longevity as a tradeoff.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to measure maximum lifespan and instead used median age of seals harvested in autumn (August-December) as an index to compare age distribution of seals in the north versus south. Previous research has indicated that the autumn hunt during the open-water season provides samples that are representative of the population age-sex distribution (Ferguson, Young, Yurkowski, Anderson, & Willing, 2017).…”
Section: Age Structurementioning
confidence: 99%
“…The probability of a seal giving birth to a pup is associated with individual body condition, which results from foraging success (Ferguson et al, 2017;Guinet, Roux, Bonnet, & Mison, 1998;Stenson, Buren, & Koen-Alonso, 2016). The mass of a mature female at the start of lactation is a proxy for body condition which can vary between years but also sets limits on maternal expenditure (the net change in maternal mass from birth to weaning of the pup) in phocid seals (Arnbom, Fedak, & Boyd, 1997).…”
Section: Introductionmentioning
confidence: 99%